The PACT advance decision-making template: preparing for Mental Health Act reforms with co-production, focus groups and consultation - Stephenson, Lucy A. (Int J Law Psychiatry, 2020)
BACKGROUND: Advance decision making (ADM) in mental health is supported by stakeholders but faces significant barriers. These must be overcome, not least to support the UK government's commitment to introduce statutory mental health ADM in England and Wales. AIMS: To build understanding and address the gap between aspirations for ADM and actuality, with feasible co-produced ADM resources. METHODS: We used focus groups and consultation to explore experience and views of stakeholders on ADM processes and materials. Discussions included feedback on an ADM template which was adapted accordingly throughout the research process. RESULTS: Between September 2017 and December 2019, 94 individuals, representing stakeholders advised on design and process of ADM, alongside wider discussion at stakeholder events. Collaborative ADM was universally supported. Valued outcomes were diverse and combining aspirations with practicality required resolving dilemmas. A prototype template and guidance, the PACT (Preferences and Advance decisions for Crisis and Treatment) was co-produced, designed to help manage fluctuating mental capacity through collaborative decision making. The PACT enables direct engagement with medico-legal frameworks, with provision to facilitate person-centred assessments, treatment refusals and requests. Resources including supported engagement and cross-agency awareness and accessibility were seen as essential. CONCLUSION: Our research confirms high stakeholder motivation to engage in ADM is hampered by multiple barriers. We identified enabling conditions for ADM and co-produced an ADM template and guidance which supports achievement of a range of valued outcomes. Further developments to support and evaluate the process of implementation are now needed to prepare for statutory change.